DAYA TERIMA DAN NILAI GIZI BISKUIT DENGAN SUBSTITUSI TEPUNG GARBANZO (Cicer arietinum L.) DAN PENAMBAHAN TEPUNG WORTEL - Dewi, Arifa Mustika; Bahar, Asrul (Jurnal Gizi dan Pangan Soedirman, 2024)
Innovation has encouraged the development of snack products such as high-fiber biscuits by substituting garbanzo flour (Cicer arietinum L.) and the addition of carrot flour. This study aims to determine the effect of the substitution of garbanzo flour, the addition of carrot flour, and the interaction of the two factors on the acceptability of biscuits based on color, aroma, taste, and crunchiness, as well as the energy and fiber content contained in the best biscuit formula based on the acceptability test results. The research was conducted experimentally, using a two-factor Completely Randomized Design (CRD). The first factor was the substitution of garbanzo flour, and the second factor was the addition of carrot flour. An acceptability test was carried out with six biscuit recipes (F1 = 40% Garbanzo Flour, 10% Carrot Flour; F2 = 40% Garbanzo Flour, 20% Carrot Flour; F3 = 60% Garbanzo Flour, 10% Carrot Flour; F4 = 60% Garbanzo Flour, 20% Carrot Flour; F5 = 80% Garbanzo Flour, 10% Carrot Flour; F6 = 80% Garbanzo Flour, 20% Carrot Flour), which were subsequently analyzed using Two-Ways Annova for parametric statistics and Duncan’s Multiple Range Test. The Acceptability Test was conducted in Tangerang and Surabaya with 50 untrained panelists. The results of the study found that there was an effect of garbanzo flour substitution on color (p=0.003) and no effect on aroma (p=0.835), crispness (p=0.136), and taste (p=0.241); there was an effect on the addition of carrot flour on color (p=0.002), aroma (p=0.000), taste (p=0.000), and crispness (p=0.000); there was an influence on the interaction between the two on color (p=0.036), aroma (p=0.047), taste (p=0.000), and crispness (p=0.013). According to SNI 01-2973-1992 Biscuits and Nutritional Adequacy Rates, the best biscuit formula based on the acceptability test is the F3 formula biscuit product which meets the criteria for low energy of 271.40 kcal (maximum 400 kcal) and high fiber of 4.01 g (minimum 0.5) per 100 g of biscuit; The selling price of biscuits per package weighing 100 g containing 16 biscuits is Rp22,000.00.